IMPLEMENTASI NIKAH FASID DAN NIKAH BATIL (Studi Kasus KUA Kec. Cempa Kab. Pinrang) - Abdul Rahim (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2017)
AbstractMarriage fasid and marriage vanity is a form of unauthorized marriage in the eyes of the laws of law and religion. In fact now, many marriages are not in accordance with the procedure and do not meet the pillars and terms of the marriage. Just based on the same likes without seeing the terms and pillars to be met before marriage. Therefore, to overcome such a thing required a principle of selectivity that is a principle in a marriage when a person who wants to marry it must select first with whom he may marry and with whom he is prohibited to marry. Kata Kunci: Nikah Fasid, Nikah Batil